IMPLICATIONS OF WAKAF AND GRANTS ON THE DISTRIBUTION OF ISLAMIC INHERITANCE: A CONTEMPORARY POSITIVE LAW AND FIQIH PERSPECTIVE - Gita, Reka Dea; Rokhim, Abdul; Farahwati; Safitri, Gusti Heliana (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study examines the influence of waqf and grants on the inheritance distribution system in Islamic law, from the perspective of Indonesian positive law and contemporary Islamic jurisprudence. In Islamic teachings, the distribution of inheritance (al-mirats) is regulated in detail through the provisions of the Qur'an and Hadith, and has received in-depth explanations in classical literature and jurisprudence. The phenomenon of grants and waqf, both before and after the death of the testator, creates its own dynamics due to the intersection of provisions of Indonesian positive law, such as the Compilation of Islamic Law (KHI), and classical and contemporary Islamic jurisprudence. Normatively, waqf and grants have different legal consequences that directly impact the rights of heirs, distributive justice, and potential disputes. This study uses a normative legal approach, examining relevant laws, doctrines, fatwas, and court decisions, to highlight the need for regulatory synergy to ensure justice, legal certainty, and social harmony in the distribution of inheritance in Indonesian Muslim society.